Z+6*z-6=5

Simple and best practice solution for Z+6*z-6=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Z+6*z-6=5 equation:


Simplifying
Z + 6z + -6 = 5

Reorder the terms:
-6 + Z + 6z = 5

Solving
-6 + Z + 6z = 5

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + Z + 6 + 6z = 5 + 6

Reorder the terms:
-6 + 6 + Z + 6z = 5 + 6

Combine like terms: -6 + 6 = 0
0 + Z + 6z = 5 + 6
Z + 6z = 5 + 6

Combine like terms: 5 + 6 = 11
Z + 6z = 11

Add '-6z' to each side of the equation.
Z + 6z + -6z = 11 + -6z

Combine like terms: 6z + -6z = 0
Z + 0 = 11 + -6z
Z = 11 + -6z

Simplifying
Z = 11 + -6z

See similar equations:

| 19-10(9+6)/25 | | -3x-15=-5 | | h=16t^2+64t | | 3x-3=9x | | 6m-3/7=15 | | y=0.42(x-8) | | W(w+12)=w(x+14)+12 | | 88=(2x-5)(x) | | 45=(.333x+2)(x) | | 6500-55*12=y | | x(x+8)=6336 | | 4x^2-81x^2=0 | | 1.6*10^5/8*10^3 | | 35x=23+30x | | 7x-8x+3x=-8 | | 4x2x3x4/6x3 | | 35x=23+5x | | 1.6*10^5/8*10 | | N/0.6=0.05/12 | | 2X^2+6X+16=0 | | (4x-8)=(4x+12) | | (v)+14=98 | | 2.2x-5=2(1.4x+2) | | 2.34+0.23=6.25 | | c^2-2c-10=0 | | -3(m+5)=9-6m | | 8k=k+49 | | (x-3)2=5 | | 1/2X+5+2/3X-4 | | .32+(-1.5)= | | x(x+8)=1280 | | -19-8a=5 |

Equations solver categories